A homozygous variant in the GPIHBP1 gene in a child with severe hypertriglyceridemia and a systematic literature review - Sustar, Ursa; Groselj, Urh; Khan, Sabeen Abid; Shafi, Saeed; Khan, Iqbal; Kovac, Jernej; Bizjan, Barbara Jenko; Battelino, Tadej; Sadiq, Fouzia (Frontiers in Genetics, 2022)
Background: Due to nonspecific symptoms, rare dyslipidaemias are frequently misdiagnosed, overlooked, and undertreated, leading to increased risk for severe cardiovascular disease, pancreatitis and/or multiple organ failures before diagnosis. Better guidelines for the recognition and early diagnosis of rare dyslipidaemias are urgently required. Methods: Genomic DNA was isolated from blood samples of a Pakistani paediatric patient with hypertriglyceridemia, and from his parents and siblings. Next-generation sequencing (NGS) was performed, and an expanded dyslipidaemia panel was employed for genetic analysis. Results: The NGS revealed the presence of a homozygous missense pathogenic variant c.230G>A (NM_178172.6) in exon 3 of the GPIHBP1 (glycosylphosphatidylinositol-anchored high-density lipoprotein-binding protein 1) gene resulting in amino acid change p.Cys77Tyr (NP_835466.2). The patient was 5.5 years old at the time of genetic diagnosis. The maximal total cholesterol and triglyceride levels were measured at the age of 10 months (850.7 mg/dL, 22.0 mmol/L and 5,137 mg/dL, 58.0 mmol/L, respectively). The patient had cholesterol deposits at the hard palate, eruptive xanthomas, lethargy, poor appetite, and mild splenomegaly. Both parents and sister were heterozygous for the familial variant in the GPIHBP1 gene. Moreover, in the systematic review, we present 62 patients with pathogenic variants in the GPIHBP1 gene and clinical findings, associated with hyperlipoproteinemia. Conclusions: In a child with severe hypertriglyceridemia, we identified a pathogenic variant in the GPIHBP1 gene causing hyperlipoproteinemia (type 1D). In cases of severe elevations of plasma cholesterol and/or triglycerides genetic testing for rare dyslipidaemias should be performed as soon as possible for optimal therapy and patient management.